Core Inflation Measures and Statistical Issues in Choosing Among Them - Silver, Mick (IMF Working Papers; Working Paper, 2006)
This paper provides an overview of statistical measurement issues relating to alternative measures of core inflation, and the criteria for choosing among them. The approaches to measurement considered include exclusion-based methods, imputation methods, limited influence estimators, reweighting, and economic modeling. Criteria for judging which approach to use include credibility, control, deviations from a smoothed reference series, volatility, predictive ability, causality and cointegration tests, and correlation with money supply. Country practice can differ in how the approaches are implemented and how their appropriateness is assessed. There is little consistency in the results of country studies to readily suggest guidelines on accepted methods.